2011
DOI: 10.1186/1475-2891-10-132
|View full text |Cite
|
Sign up to set email alerts
|

The "Snacking Child" and its social network: some insights from an italian survey

Abstract: BackgroundThe hypothesis underlying this work is that the social network of a child might have an impact on the alimentary behaviors, in particular for what concerns snack consumption patterns.Methods1215 Italian children 6-10 ys old were interviewed using a CATI facility in January 2010. 608 "snackers" and 607 "no-snackers" were identified. Information regarding family composition, child and relatives BMI, mother perception of child weight, child, father and mother physical activity, TV watching, social netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 30 publications
5
19
0
1
Order By: Relevance
“…19,[21][22][23] Of further concern, there is evidence that energy-dense, nutrient-poor snack foods and beverages are widely available in various settings where young people spend their time. [14][15][16][17][18][24][25][26][27][28] The majority of studies that investigated whether there is a relationship between snacking behavior and weight status either found no association 19,33,[41][42][43]45,46,48,49,[52][53][54]59 or found evidence indicating that young people who more often consumed food or beverages between meals were less likely to be obese. 21,30,32,34,37,38,55,57 However, a smaller number of studies found evidence indicating the frequency of snacking, percentage of energy consumed at snacks, or greater consumption of energy-dense snack foods was associated with increased risk for obesity among some groups, 31,35,36,44,47,50,51,56,58 and two studies found that more frequent snacking in front ...…”
Section: Discussionmentioning
confidence: 99%
“…19,[21][22][23] Of further concern, there is evidence that energy-dense, nutrient-poor snack foods and beverages are widely available in various settings where young people spend their time. [14][15][16][17][18][24][25][26][27][28] The majority of studies that investigated whether there is a relationship between snacking behavior and weight status either found no association 19,33,[41][42][43]45,46,48,49,[52][53][54]59 or found evidence indicating that young people who more often consumed food or beverages between meals were less likely to be obese. 21,30,32,34,37,38,55,57 However, a smaller number of studies found evidence indicating the frequency of snacking, percentage of energy consumed at snacks, or greater consumption of energy-dense snack foods was associated with increased risk for obesity among some groups, 31,35,36,44,47,50,51,56,58 and two studies found that more frequent snacking in front ...…”
Section: Discussionmentioning
confidence: 99%
“…Children like to consume products they know -the more often children eat a given product, the more they like it. Children familiarize themselves with new tastes and products through experience as well as by observing dietary behaviours of other people present in their environment (parents, siblings, peers) (4,31,34,35) . The present study confirmed the role of the influence exerted by the family environment and health-oriented attitudes of parents (parents eating F&V, encouraging children to eat F&V, giving sliced F&V between meals, giving children F&V to take to school) on the F&V consumption of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Because the epidemiologic evidence of the inverse relation between meal frequency and BMI is considered extremely weak, new controlled studies are needed (39). Present conflicting findings may also be the result of the lack of uniformity in the definition of snack (13). Our most compelling result is the association between timing of the large snack and overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have, however, failed to establish a correlation between snacking and overweight (9)(10)(11)(12)(13)(14). Such variability could be explained by the definition variability of ''snack'' (13).…”
mentioning
confidence: 97%
See 1 more Smart Citation